Substituted phthalocyanines development and self-assembled monolayer sensor studies - Matemadombo, Fungisai (Rhodes University, Faculty of Science, Department of Chemistry, 2006)
Zinc, cobalt and iron phenylthio substituted phthalocyanines have been synthesized and characterized. Cyclic and square wave voltammetry in dimethylformamide containing tetrabutylammonium perchlorate revealed five and six redox processes respectively for the cobalt and iron phenylthio substituted phthalocyanines. These complexes are easier to reduce compared to the corresponding unsubstituted MPc and to butylthio substituted derivatives. Spectroelectrochemistry (in dimethylformamide containing tetrabutylammonium perchlorate) was employed to assign the cyclic voltammetry peaks, and gave spectra characteristic of Fe(I)Pc for reduction of iron phenylthio substituted phthalocyanine and Co(I)Pc for the reduction of cobalt phenylthio substituted phthalocyanine. The spectrum of the former is particularly of importance since such species have not received much attention in literature. Cobalt and iron phenylthio substituted phthalocyanines have been deposited on Au electrode surfaces through the self assembled monolayer (SAM) technique. The so formed layers were studied using voltammetric techniques. These SAMs blocked a number of Faradic processes and electrocatalyzed the oxidation of L-cysteine. Amine substituted cobalt phthalocyanine (CoTAPc) was deposited on gold surfaces by using an interconnecting SAM of mercaptopropionic acid or dithiobis(N-succinimidyl propionate) through the creation of an amide. Reductive and oxidative desorption of the SAMs limit the useful potential window. The SAM-CoTAPc layers show electrocatalytic activities towards oxygen reduction through the Co(I) central metal ion. Both SAMs were highly stable and hence will be interesting tools for further research in surface modification and sensor development.
Keywords: Phthalocyanines; Monomolecular films; Electrochemistry; Spectrum analysis